Improvement of myofibrillar protein gel strength of Scomberomorus niphonius by riboflavin under UVA irradiation. Issue 4 (20th February 2020) - He, Baoyu; Shi, Yixin; Jin, Meiran; Pu, Yuan; Dong, Xiuping; Yu, Chenxu; Qi, Hang
Abstract: In this study, effects of different concentrations of riboflavin (0, 0.02, and 0.1 μmol/g protein) on myofibrillar protein (MP, Scomberomorus niphonius ) gel were characterized. The gel structure and properties were studied with or without Ultraviolet A (UVA) irradiation. Electron spin resonance results showed that riboflavin produced · OH under UVA irradiation, which subsequently oxidized the MP. Compared with the control group, the addition of riboflavin with UVA irradiation increased the strength of the MP gel. The rheological results showed that under UVA irradiation, addition of riboflavin facilitated the sol–gel transition between 45 and 52°C, indicating that oxidation led to significant structural changes which in turn resulted in a more compact and uniform gel network. The presence of riboflavin led to increased carbonyl content and decreased sulfhydryl and free amino groups, which decreased the protein solubility and promoted alpha‐helical conformational loss in the secondary structure of the MP. These results all indicated that the MP has been oxidized. Electrophoresis revealed that myosin heavy chains were aggregated in the UVA‐treated riboflavin‐added MP gel, indicating that protein cross‐linking has been induced. All the results indicated that the · OH produced by riboflavin under UVA irradiation oxidized the MP, and improved protein crosslinking and gel properties.